Longevity of Humoral Response Six Months Following BNT162b2 Vaccine in Dialysis Patients - Agur, Timna; Ben-Dor, Naomi; Herman-Edelstein, Michal; Steinmetz, Tali; Lichtenberg, Shelly; Schneider, Shira; Yahav, Dafna; Rozen-Zvi, Benaya; Zingerman, Boris (Frontiers in Medicine, 2022)
End-stage kidney disease substantially increases the risk of severe COVID-19. However, despite early robust immunogenicity of the mRNA-SARS-COV-2 vaccination in hemodialysis patients, the longevity of humoral response in this high-risk population is still unknown. A prospective cohort study aimed to evaluate the longevity of serologic response in hemodialysis patients, compared with a control group, six months following the second dose of the BNT162b2 vaccine. We assessed antibody response by quantitative measurement of IgG antibodies against the receptor-binding domain of the Spike protein (Anti-S1-RBD IgG). Study outcomes were defined as seropositivity rate and log-transformed Anti-S1-RBD IgG levels at six-months, and the change in antibody levels between 3 to 6 months. The cohort included 104 hemodialysis patients and 84 controls. At a median time of 184 days (IQR 183-188) following the second dose of the vaccine, 83/104 (79.8%) hemodialysis patients maintained seropositivity for Anti-S1-RBD IgG level compared to 83/84 (98.8%) in the control group (p<0.001). The log-transformed antibody level was significantly lower in the hemodialysis group (2.23±0.39 log AU/ml vs. 2.69±0.65 log AU/ml respectively, p<0.001). Older age and hypoalbuminemia were the only variables that were found to be associated with reduced log-transformed antibody levels in univariate and multivariate analysis. There was no interaction between dialysis status and antibody level decline rate (p=0.972) Among hemodialysis patients, seropositivity rate and Anti-S1-RBD antibody titers were substantially reduced compared with a control group, at 6-months following the second dose of the BNT162b2 vaccine. These findings support the prioritization of hemodialysis patients for a third “booster” dose.